Does competition reduce price discrimination? New evidence from the airline industry - Christopher Gerardi; Adam Hale Shapiro (Federal Reserve Bank of Boston, 2007)
This paper analyzes the effects of market structure on price dispersion in the airline industry, using panel data from 1993 through 2006. The results found in this paper contrast with those of Borenstein and Rose (1994), who found that price dispersion increases with competition. We find that competition has a negative effect on price dispersion, in line with the traditional textbook treatment of price discrimination. Specifically, the effects of competition on price dispersion are most significant on routes that we identify as having consumers characterized by relatively heterogeneous elasticities of demand. On routes with a more homogeneous customer base, the effects of competition on price discrimination are largely insignificant. We conclude from these results that competition acts to erode the ability of a carrier to price discriminate, resulting in reduced overall price dispersion.
Keywords: D43; L13; L93; 330; Luftverkehr; Verkehrstarif; Wettbewerb; USA